The Role of the ω‐3 Fatty Acid DHA in the Human Life Cycle. Issue 1 (27th November 2012) - Carlson, Sarah J.; Fallon, Erica M.; Kalish, Brian T.; Gura, Kathleen M.; Puder, Mark
Abstract : Dietary consumption of the essential fatty acids linoleic acid (LA; ω‐6) and α‐linolenic acid (ALA; ω‐3) is necessary for human growth and development. In the past 150 years, the average Western diet has changed dramatically such that humans today consume a much higher proportion of ω‐6 fatty acids relative to ω‐3 fatty acids than ever before. The importance of ω‐3 fatty acids in human development has been well established in fetal and neonatal development, with brain and retinal tissues highly dependent on ω‐3 fatty acids, specifically docosahexaenoic acid (DHA) for membrane fluidity and signal transduction. In childhood, ω‐3s have been shown to contribute to ongoing cognitive development and may be involved in metabolic programming of bone turnover and adipogenesis. ω‐3s may also play important roles in adult neurophysiology and disease prevention.